Implementasi Permainan Tradisional Cublak- Cublak Suweng Sebagai Penguat Karakter Sosial Siswa MI - Nurdiana Alfina Damayanti; Oky Ristya Trisnawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
Nurdiana Alfina Damayanti 2112013 Implementation of the Traditional Game Cublak-Cublak Suweng as Strengthening the Social Character of Mi Students The purpose of this study is to strengthen the social character of Grade 1 Mi students in Javanese language subjects through the traditional game cublak-cublak suweng. The background of this research is that the social character of class 1Mi Pejagatan students tends to be low because basically first grade students still need a lot of direction from the teacher. This study is Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of four stages, namely: planning, implementation, observation and reflection. The subjects of this research were 17 grade 1 students at MI Pejagatan. Data collection techniques include observation, tests, interviews and documentation. The tests used were tests not in the form of questions but in the form of three observation tests, an attitude scale test and a performance test given in the form of a pre-test at the start of the research and a post-test at the end of cycle II, as well as a rubric for assessing students' social character. The research study showed a significant increase from cycle I to cycle II. The average score of students' social character increased from 68.75% in the pre-test to 81.1% in the Cycle II post-test. This research is also strengthened by the classical completion percentage from Cycle 1 student observations from 50% to 69% in Cycle 2 and Teacher Observations in Cycle 1 from 68% to 91% at the end of Cycle II. This increase can be seen surging in every aspect of cooperation, honesty, discipline, responsibility. Based on the results of this research, it can be concluded that the use of traditional media cublak-cublak suweng is able to strengthen the social character of class 1 Mi students. The use of the traditional game media cublak-cublak suweng is able to give grade 1 students the freedom to develop their character.